Pengaruh Konsentrasi Antitranspiran Chitosan Terhadap Pembuahan dan Produksi Salak Gula Pasir di Luar Musim - I KETUT SUNARKA; I NYOMAN RAI; NI LUH KARTINI (Agrotrop : Journal on Agriculture Science, 2015)
The Effect of Antitranspirant Chitosan Consentrantions to Fruit-Set and Production ff Salacca zalacca var. Gula Pasir on Off-Season. Salak Gula Pasir (Salacca zalacca var. Gula Pasir) naturally flowering once every three months or four times a year. During the four times flowering, the best harvest or fruit production only once a year while the other three flowering are failed become a fruit-set. The failure was caused by rainfall and low rainy time. This research aimed to know the effect of several Antitranspirant Chitosan Consentrations to the success of flower to become a fruit (fruit-set) on Salacca zalacca var. Gula Pasir. This research used random sampling where the area was divided into four Antitranspirant Chitosan Consentrations. The factor of Antitranspirant Chitosan Consentrations consists of four levels (0%, 15%, 30%, and 45%). The research was conducted at the central production of Salacca zalacca var. Gula Pasir in Sibetan Village, Bebandem District, Karangasem Regency. The result of giving Antitranspirant Chitosan Consentrations at 45% was effective improved the success of flower to become a fruit-set of 64,48% on Gadu Season while on Sela II Season it effective improved 84,38% at the 30% consentrations.